CF@conductive MOF@Fe3O4 three-layer composite wave-absorbing film, preparation method and application thereof
Patent Information
- Application Number
- CN202611468246.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
多界面极化弛豫、电导损耗、磁损耗、涡流损耗与多孔散射损耗形成高效协同耦合,解决传统材料阻抗失配、损耗单一、频带窄的问题,最终实现材料轻质、柔性、宽频、高效强吸波的综合性能提升
(1)本发明采用静电纺丝、水热原位生长、化学共沉淀相结合的制备工艺。首先采用静电纺丝与高温碳化相结合制备碳纤维作为基底,碳纤维具有轻质、柔性、高导电性等特点,其三维网络结构有利于电磁波的多重散射。通过混酸处理在碳纤维表面引入含氧官能团,从而为后续MOF原位生长提供成核位点。其次,以金属盐和HHTP为原料,通过水热法在碳纤维表面原位生长未碳化的本征导电MOF层,该过程保留了MOF固有的晶体拓扑结构、规整贯通孔道与金属-有机配位环境,避免传统高温碳化破坏MOF本征结构的缺陷,使导电MOF能够充分发挥有序晶体界面极化与孔道散射损耗的优势。最后,采用化学共沉淀法以三价铁盐和二价铁盐为铁源、氨水为沉淀剂,在CF@导电MOF表面原位生成并负载Fe3O4纳米颗粒,Fe3O4与导电MOF之间形成紧密接触的异质界面,增强界面极化效应。各步骤的工艺参数相互配合,使三层结构均匀、可控地逐层构建,最终协同解决传统吸波材料阻抗失配、损耗机制单一、吸波频带窄的技术问题。
Smart Images

Figure CN122980218A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of microwave absorbing materials technology, specifically relating to a flexible, lightweight, high-efficiency, and broadband CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing material, its preparation method, and its application. Background Technology
[0002] Radar absorbing materials not only need to possess high absorption performance and wide bandwidth, but also need to be lightweight, flexible, and thin. Carbon fiber, due to its lightweight, high strength, and high conductivity, is widely used in the fabrication of radar absorbing materials to achieve radar stealth. However, due to its high dielectric constant, carbon fiber often exhibits significant impedance mismatch with free space. To overcome this problem, existing technologies typically introduce other components inside or outside the carbon fiber, including strategies such as surface functionalization modification, porous structure design, constructing core-shell or core-sheath structures, hollow design, and forming heterojunctions with other materials.
[0003] Metal-organic frameworks (MOFs) possess advantages such as lightweight, high specific surface area, rich topological structures, tunable pores, and ease of functionalization. Currently, many researchers use them as sacrificial precursors, pyrolyzing them to obtain metal or metal compound / porous carbon composites to improve the impedance matching properties of carbon fibers. However, this carbonization process has inherent drawbacks: high-temperature carbonization irreversibly destroys the intrinsic long-range ordered crystal topology, regular interconnected pores, and metal-organic coordination microenvironment of MOFs, resulting in a product that is merely a mixed system of disordered carbon skeletons and agglomerated metal particles, losing the structural designability and interfacial order of MOFs. The advantages of carbonized products in microwave absorption modulation cannot be replaced by those of uncarbonized conductive MOFs: Uncarbonized conductive MOFs possess ordered lattices and stable coordination active sites, which can generate uniform and controllable interfacial polarization and dipole polarization relaxation under an external electromagnetic field, forming stable dielectric loss; their regular channels can construct ordered electromagnetic wave scattering channels, extending the path length and improving attenuation efficiency, while precisely controlling the material conductivity to optimize impedance matching; in addition, the high-temperature pyrolysis process is complex, energy-intensive, and has poor batch stability, which is not conducive to large-scale preparation. Therefore, traditional carbonized MOF-derived materials are a technical route that abandons the intrinsic structural advantages of MOFs, and the performance modulation capability is limited. However, currently, due to the strong chemical inertness of carbon fiber surfaces, in-situ growth of MOFs is difficult, crystals are prone to agglomeration and shedding, and the uniformity of the composite layer is difficult to control. Therefore, the technology for in-situ growth of uncarbonized conductive MOFs on carbon fiber surfaces is limited; at the same time, the types of intrinsically conductive MOFs that can be used for microwave absorption are limited, restricting the practical application of this approach.
[0004] In addition, existing studies generally suffer from problems such as single component, limited number of heterogeneous interfaces, and poor structural controllability, making it difficult to achieve synergistic matching of dielectric loss and magnetic loss. This results in defects such as a single electromagnetic wave attenuation mode, poor control flexibility, insufficient magnetic loss, and a narrow effective absorption frequency band. Summary of the Invention
[0005] One objective of this invention is to provide a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film. This invention utilizes a combination of electrospinning, hydrothermal in-situ growth, and chemical co-precipitation processes to produce a composite material that overcomes the bottleneck of single-loss through a multi-interface, multi-component synergistic mechanism. The carbon fiber substrate provides a continuous conductive network and basic dielectric loss. The intermediate uncarbonized conductive MOF layer achieves impedance matching, controllable interface polarization, and multiple wave scattering through ordered crystal interfaces and porous structures. The surface Fe3O4 nanoparticles provide magnetic loss. This three-layer structure constructs an ordered and controllable hierarchical heterogeneous interface. Multi-interface polarization relaxation, conductivity loss, magnetic loss, eddy current loss, and porous scattering loss form a highly efficient synergistic coupling, solving the problems of impedance mismatch, single loss, and narrow bandwidth inherent in traditional materials. Ultimately, this achieves a comprehensive improvement in the material's lightweight, flexible, wide-bandwidth, and highly efficient microwave absorption performance.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film, comprising the following steps: Step 1: Dissolve the polymer in an organic solvent, mix and stir until clear to obtain an electrospinning solution, electrospin to obtain a polymer film, then pre-oxidize and carbonize the polymer film at high temperature to obtain carbon fiber, then heat, wash and dry the carbon fiber in a mixed acid system to obtain mixed acid treated carbon fiber. Step 2: Dissolve the metal salt and 2,3,6,7,10,11-hexahydroxytribenzene in deionized water, then add carbon fibers treated with mixed acid, place in a sealed reaction vessel and heat, naturally cool to room temperature, wash with acetone and deionized water, and vacuum dry to load a conductive MOF on the surface of the carbon fiber matrix, denoted as CF@conductive MOF film. Step 3: Using a chemical co-precipitation method, ferric salts and ferrous salts are used as iron sources, and 25wt% ammonia water is used as a precipitant. The CF@conductive MOF membrane is added and stirred in a water bath. After the reaction is completed, the membrane is washed multiple times with deionized water and anhydrous ethanol, and then vacuum dried. Fe3O4 nanoparticles are loaded on the surface of the conductive MOF in the CF@conductive MOF membrane to obtain the CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing membrane.
[0007] Further improvements to the preparation method of CF@conductive MOF@Fe3O4 three-layer composite absorbing film: Preferably, the polymer in step 1 is polyacrylonitrile, the organic solvent is N,N-dimethylformamide, and the mixed acid system is sulfuric acid and nitric acid; the metal salt in step 2 is one or more of zinc acetate, copper acetate, cobalt acetate, and nickel acetate; the trivalent ferric salt in step 3 is ferric chloride hexahydrate, and the divalent ferric salt is ferrous chloride tetrahydrate.
[0008] Preferably, the electrospinning solution contains 10-15% polyacrylonitrile by mass, the molecular weight of the polyacrylonitrile is 150,000, the stirring speed is 1000-1100 r / min, and the stirring time is 10-12 h.
[0009] Preferably, the parameters for electrospinning in step 1 are: voltage of 15-20 kV, solution propulsion rate of 0.1-0.15 mm / min, receiving distance of 10-25 cm, temperature of 22-30 ℃, and humidity of 45-55%.
[0010] Preferably, the parameters for the pre-oxidation process in step 1 are: temperature 230-260 ℃, holding time 1-3 h; and the parameters for the high-temperature carbonization process are: temperature 700-900 ℃, holding time 3-5 h, atmosphere is nitrogen or argon, and heating rate is 2-5 ℃ / min.
[0011] Preferably, in the mixed acid system of step 1, the mixing volume ratio of sulfuric acid and nitric acid is (2-4):1, the mass concentration of sulfuric acid is 95.0% to 98.0%, the mass concentration of nitric acid is 65.0% to 68.0%, the heating temperature of carbon fiber in the mixed acid system is 30-70 ℃, the heating time is 1-4 h, and the size of carbon fiber is 2cm×4cm.
[0012] Preferably, in step 2, the amount of metal salt used is 0.035-0.045 g, the amount of 2,3,6,7,10,11-hexahydroxytriphenyl is 0.025-0.030 g, the amount of deionized water is 14-18 mL, the heating temperature is 80-90 ℃, and the heating time is 10-14 h.
[0013] Preferably, in step 3, the amount of ferric chloride hexahydrate is 0.6-0.9 g, the amount of ferrous chloride tetrahydrate is 0.3-0.5 g, the amount of deionized water is 70-90 mL, the amount of 25wt% ammonia water is 8-10 mL, and the temperature of the water bath stirring is 50-70℃ and the time is 1-3 h. The vacuum drying temperature in steps 2 and 3 is 50-70 ℃, and the drying time is 10-12 h.
[0014] The second objective of this invention is to provide a CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared by any one of the above-described methods.
[0015] The third objective of this invention is to provide an application of the above-mentioned CF@conductive MOF@Fe3O4 three-layer composite absorbing film in the field of microwave absorption. The CF@conductive MOF@Fe3O4 three-layer composite absorbing film is mixed with paraffin wax at a mass ratio of (10-25):100, and then placed in a mold to press into a coaxial ring with an inner diameter of 3.04 mm and an outer diameter of 7.0 mm.
[0016] The advantages of this invention compared to the prior art are as follows: (1) This invention employs a preparation process combining electrospinning, hydrothermal in-situ growth, and chemical coprecipitation. First, carbon fibers are prepared as a substrate using a combination of electrospinning and high-temperature carbonization. Carbon fibers are lightweight, flexible, and highly conductive, and their three-dimensional network structure is conducive to the multiple scattering of electromagnetic waves. Oxygen-containing functional groups are introduced onto the carbon fiber surface through mixed acid treatment, thereby providing nucleation sites for subsequent in-situ MOF growth. Second, using metal salts and HHTP as raw materials, an uncarbonized intrinsically conductive MOF layer is grown in situ on the carbon fiber surface via a hydrothermal method. This process preserves the inherent crystal topology, regular interconnected channels, and metal-organic coordination environment of MOF, avoiding the defects of traditional high-temperature carbonization that destroy the intrinsic structure of MOF, enabling the conductive MOF to fully utilize the advantages of ordered crystal interface polarization and channel scattering loss. Finally, a chemical co-precipitation method was employed, using ferric and ferrous salts as iron sources and ammonia as a precipitant, to generate and load Fe3O4 nanoparticles in situ on the surface of CF@conductive MOF. This resulted in a tightly packed heterogeneous interface between Fe3O4 and the conductive MOF, enhancing the interfacial polarization effect. The process parameters of each step were coordinated to ensure the uniform and controllable layer-by-layer construction of the three-layer structure, ultimately synergistically solving the technical problems of impedance mismatch, simplistic loss mechanisms, and narrow absorption bandwidth inherent in traditional microwave absorbing materials.
[0017] (2) The CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared in this invention has a conductive MOF layer loaded on the surface of a carbon fiber substrate, and Fe3O4 nanoparticles loaded on the surface of the conductive MOF layer, forming a three-layer core-shell structure consisting of carbon fiber, conductive MOF, and Fe3O4 from the inside out. In this structural design, the carbon fiber substrate provides a continuous conductive network and basic dielectric loss; the middle uncarbonized conductive MOF layer relies on the ordered crystal interface and regular through-hole structure to achieve impedance matching, controllable interface polarization, and multiple wave scattering; the surface Fe3O4 nanoparticles provide magnetic loss and eddy current loss. An ordered and controllable hierarchical heterogeneous interface is formed between the three layers, and the multi-interface polarization relaxation, conductivity loss, magnetic loss, eddy current loss, and porous scattering loss form an efficient synergistic coupling to obtain good impedance matching.
[0018] (3) The CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared by this invention has excellent microwave absorption performance. Tested using a vector network analyzer (coaxial loop method, inner diameter 3.04 mm, outer diameter 7.0 mm, CF@conductive MOF@Fe3O4 three-layer composite absorbing film mixed with paraffin at a mass ratio of (10-25):100), this material exhibits good absorption performance in the 2~18 GHz range. Specifically, when the matching thickness is 3.39 mm, the lowest reflection loss at 9.84 GHz (X-band) reaches -71.46 dB; when the matching thickness is 1.98 mm, the effective absorption bandwidth can reach 7.95 GHz (8.3~16.25 GHz), covering most of the X-band and Ku-band. The composite absorbing film obtained by this invention has the characteristics of thinness, light weight, flexibility, high efficiency, and wide bandwidth, making it suitable for the microwave absorption field. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0020] Figure 1 This is a flowchart illustrating the preparation of the CF@conductive MOF@Fe3O4 film according to the present invention; Figure 2 SEM images of the CF@conductive MOF film (a) and the CF@conductive MOF@Fe3O4 film (b) prepared in Example 1 of this invention; Figure 3 The image shows the reflection loss of the CF@conductive MOF@Fe3O4 film prepared in Example 1 of this invention at different thicknesses. Figure 4 The image shows the reflection loss of the CF@conductive MOF@Fe3O4 film prepared in Example 2 of this invention at different thicknesses. Figure 5 The image shows the reflection loss of the CF@conductive MOF@Fe3O4 film prepared in Example 3 of this invention at different thicknesses. Figure 6 The image shows the reflection loss of the CF@conductive MOF@Fe3O4 film prepared in Example 4 of this invention at different thicknesses. Figure 7 The image shows the reflection loss of the CF@conductive MOF@Fe3O4 film prepared in Example 5 of this invention at different thicknesses. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0022] Example 1 This embodiment provides a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film. The preparation process is as follows: Figure 1 As shown, the specific steps include the following: Step 1, Preparation of carbon fibers: 1.2 g of polyacrylonitrile (PAN, molecular weight 150,000) was dissolved in 10 mL of N,N-dimethylformamide (DMF) and stirred at 1000 r / min for 12 h until clear, obtaining an electrospinning solution. Electrospinning parameters: voltage 15 kV, feed rate 0.12 mm / min, receiving distance 15 cm, temperature 25 ℃, humidity 50%, to obtain a PAN film. The PAN film was pre-oxidized in air at 250 ℃ for 2 h; then carbonized in a nitrogen atmosphere at 800 ℃ for 4 h at a heating rate of 2 ℃ / min to obtain carbon fibers with dimensions of 2 cm × 4 cm. The carbon fibers were placed in a mixed acid system of sulfuric acid:nitric acid = 3:1, heated at 60 ℃ for 1 h, washed with deionized water until neutral, and dried for later use.
[0023] Step 2, Preparation of CF@conductive MOF membrane: Weigh 0.040 g zinc acetate and 0.028 g 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), dissolve in 16 mL deionized water, add the acid-treated carbon fibers, hydrothermally heat at 85 ℃ for 12 h, and allow to cool naturally. Wash successively with acetone and deionized water, and vacuum dry at 60 ℃ for 12 h to obtain the CF@conductive MOF membrane.
[0024] Step 3, Preparation of CF@Conductive MOF@Fe3O4 membrane: Weigh 0.81 g of ferric chloride hexahydrate and 0.40 g of ferrous chloride tetrahydrate, dissolve them in 80 mL of deionized water, stir to dissolve, and then place the CF@conductive MOF membrane in the solution for static adsorption. Slowly add 9 mL of 25% ammonia solution, and stir in a 60℃ water bath for 2 h. Wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 60℃ for 12 h to obtain the CF@conductive MOF@Fe3O4 composite membrane.
[0025] Figure 2 These are scanning electron microscope (SEM) images of the CF@conductive MOF film and the CF@conductive MOF@Fe3O4 film prepared in Example 1 of this invention; Figure 2 It can be seen that conductive MOF was successfully loaded on the surface of carbon fiber matrix and Fe3O4 was successfully loaded on the surface of CF@conductive MOF.
[0026] Example 2 This embodiment provides a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film. The preparation process is as follows: Figure 1 As shown, the specific steps include the following: Step 1, Preparation of carbon fibers: 1.0 g of polyacrylonitrile (PAN, molecular weight 150,000) was dissolved in 10 mL of N,N-dimethylformamide (DMF) and stirred at 1000 r / min for 12 h until clear, obtaining an electrospinning solution. Electrospinning parameters: voltage 15 kV, feed rate 0.10 mm / min, receiving distance 10 cm, temperature 22 ℃, humidity 45%, to obtain a PAN film. The PAN film was pre-oxidized in air at 230 ℃ for 3 h; then carbonized in a nitrogen atmosphere at 700 ℃ for 5 h at a heating rate of 2 ℃ / min to obtain carbon fibers with dimensions of 2 cm × 4 cm. The carbon fibers were placed in a mixed acid system of sulfuric acid:nitric acid = 2:1, heated at 30 ℃ for 4 h, washed with deionized water until neutral, and dried for later use.
[0027] Step 2, Preparation of CF@conductive MOF film: Weigh 0.035 g copper acetate and 0.025 g HHTP, dissolve them in 14 mL deionized water, add the above-mentioned acid-treated carbon fibers, hydrothermally heat at 80 ℃ for 14 h, and then cool naturally. Wash with acetone and deionized water successively, and vacuum dry at 50 ℃ for 12 h to obtain CF@conductive MOF film.
[0028] Step 3, Preparation of CF@Conductive MOF@Fe3O4 membrane: Weigh 0.60 g of ferric chloride hexahydrate and 0.30 g of ferrous chloride tetrahydrate, dissolve them in 70 mL of deionized water, stir to dissolve, and then place the CF@conductive MOF membrane in the solution for static adsorption. Slowly add 8 mL of 25% ammonia solution, and stir in a 50℃ water bath for 3 h. Wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 50℃ for 12 h to obtain the CF@conductive MOF@Fe3O4 composite membrane.
[0029] Example 3 This embodiment provides a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film. The preparation process is as follows: Figure 1 As shown, the specific steps include the following: Step 1, Preparation of carbon fibers: 1.5 g of polyacrylonitrile (PAN, molecular weight 150,000) was dissolved in 10 mL of N,N-dimethylformamide (DMF) and stirred at 1100 r / min for 10 h until clear, obtaining an electrospinning solution. Electrospinning parameters: voltage 20 kV, feed rate 0.15 mm / min, receiving distance 25 cm, temperature 30 ℃, humidity 55%, to obtain a PAN film. The PAN film was pre-oxidized in air at 260 ℃ for 1 h; then carbonized in an argon atmosphere at 900 ℃ for 3 h at a heating rate of 5 ℃ / min to obtain carbon fibers with a size of 2 cm × 4 cm. The carbon fibers were placed in a mixed acid system of sulfuric acid:nitric acid = 4:1, heated at 70 ℃ for 1 h, washed with deionized water until neutral, and dried for later use.
[0030] Step 2, Preparation of CF@conductive MOF film: Weigh 0.045 g cobalt acetate and 0.030 g HHTP, dissolve them in 18 mL deionized water, add the above-mentioned acid-treated carbon fibers, hydrothermally heat at 90 ℃ for 10 h, and then cool naturally. Wash with acetone and deionized water successively, and vacuum dry at 70 ℃ for 10 h to obtain CF@conductive MOF film.
[0031] Step 3, Preparation of CF@Conductive MOF@Fe3O4 membrane: Weigh 0.90 g of ferric chloride hexahydrate and 0.50 g of ferrous chloride tetrahydrate, dissolve them in 90 mL of deionized water, stir to dissolve, and then place the CF@conductive MOF membrane in the solution for static adsorption. Slowly add 10 mL of 25% ammonia solution, and stir in a 70℃ water bath for 1 h. Wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 70℃ for 10 h to obtain the CF@conductive MOF@Fe3O4 composite membrane.
[0032] Example 4 This embodiment provides a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film. The preparation process is as follows: Figure 1 As shown, the specific steps include the following: Step 1, Preparation of carbon fibers: 1.3 g of polyacrylonitrile (PAN, molecular weight 150,000) was dissolved in 10 mL of N,N-dimethylformamide (DMF) and stirred at 1050 r / min for 11 h until clear, obtaining an electrospinning solution. Electrospinning parameters: voltage 18 kV, feed rate 0.11 mm / min, receiving distance 20 cm, temperature 26 ℃, humidity 48%, to obtain a PAN film. The PAN film was pre-oxidized in air at 240 ℃ for 2 h; then carbonized in a nitrogen atmosphere at 750 ℃ for 4 h at a heating rate of 3 ℃ / min to obtain carbon fibers with dimensions of 2 cm × 4 cm. The carbon fibers were placed in a mixed acid system of sulfuric acid:nitric acid = 2.5:1, heated at 45 ℃ for 2.5 h, washed with deionized water until neutral, and dried for later use.
[0033] Step 2, Preparation of CF@conductive MOF film: Weigh 0.038 g nickel acetate and 0.026 g HHTP, dissolve them in 15 mL deionized water, add the above-mentioned acid-treated carbon fibers, hydrothermally heat at 82 ℃ for 13 h, and then cool naturally. Wash with acetone and deionized water successively, and vacuum dry at 55 ℃ for 11 h to obtain CF@conductive MOF film.
[0034] Step 3, Preparation of CF@Conductive MOF@Fe3O4 membrane: Weigh 0.72 g of ferric chloride hexahydrate and 0.35 g of ferrous chloride tetrahydrate, dissolve them in 76 mL of deionized water, stir to dissolve, and then place the solution into a CF@conductive MOF membrane for static adsorption. Slowly add 8.2 mL of 25% ammonia water, and stir in a 58℃ water bath for 2.2 h. Wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 55 ℃ for 11 h to obtain the CF@conductive MOF@Fe3O4 composite membrane.
[0035] Example 5 This embodiment provides a method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film. The preparation process is as follows: Figure 1 As shown, the specific steps include the following: Step 1, Preparation of carbon fibers: 1.4 g of polyacrylonitrile (PAN, molecular weight 150,000) was dissolved in 10 mL of N,N-dimethylformamide (DMF) and stirred at 1080 r / min for 10.5 h until clear, obtaining an electrospinning solution. Electrospinning parameters: voltage 17 kV, feed rate 0.14 mm / min, receiving distance 22 cm, temperature 28 ℃, humidity 52%, to obtain a PAN film. The PAN film was pre-oxidized in air at 255 ℃ for 1.5 h; then carbonized in a nitrogen atmosphere at 850 ℃ for 3.5 h at a heating rate of 4 ℃ / min to obtain carbon fibers with dimensions of 2 cm × 4 cm. The carbon fibers were placed in a mixed acid system of sulfuric acid:nitric acid = 3.5:1 and heated at 52 ℃ for 2 h, washed with deionized water until neutral, and dried for later use.
[0036] Step 2, Preparation of CF@conductive MOF film: Weigh 0.042 g nickel acetate and 0.029 g HHTP, dissolve them in 17 mL deionized water, add the above-mentioned acid-treated carbon fibers, hydrothermally heat at 88 ℃ for 11 h, and then cool naturally. Wash with acetone and deionized water successively, and vacuum dry at 65 ℃ for 10.5 h to obtain CF@conductive MOF film.
[0037] Step 3, Preparation of CF@Conductive MOF@Fe3O4 membrane: Weigh 0.85 g of ferric chloride hexahydrate and 0.46 g of ferrous chloride tetrahydrate, dissolve them in 86 mL of deionized water, stir to dissolve, and then place the solution into a CF@conductive MOF membrane for static adsorption. Slowly add 9.4 mL of 25% ammonia water, and stir in a 66℃ water bath for 1.8 h. Wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 65℃ for 10.5 h to obtain the CF@conductive MOF@Fe3O4 composite membrane.
[0038] Performance testing The CF@conductive MOF@Fe3O4 three-layer composite absorbing films prepared in Examples 1-5 were mixed with paraffin wax in a certain proportion, placed in a mold, and pressed into a coaxial ring with an inner diameter of 3.04 mm and an outer diameter of 7.0 mm. The electromagnetic parameters of the coaxial ring in the range of 2~18 GHz were tested using a vector network analyzer (3671D, Ceyear), and its reflection loss was calculated based on the measured electromagnetic parameters.
[0039] The CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared in Example 1 was mixed with paraffin at a mass ratio of 25:100, placed in a mold, and pressed into a coaxial ring. Figure 3 This is a reflection loss diagram of the CF@conductive MOF@Fe3O4 film prepared in Example 1 of this invention at different thicknesses; Figure 3 It can be seen that when the matching thickness is 3.39 mm, the lowest reflection loss (RL) at 9.84 GHz (X-band) is... min The effective absorption bandwidth (EAB) is -71.46 dB, and when the matching thickness is 2.61 mm, the effective absorption bandwidth (EAB) is 6.48 GHz (11.52-18 GHz), covering part of the X-band and the entire Ku-band.
[0040] The CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film prepared in Example 2 was mixed with paraffin at a mass ratio of 10:100, placed in a mold, and pressed into a coaxial ring. Figure 4 This is a reflection loss diagram of the CF@conductive MOF@Fe3O4 film prepared in Example 2 of the present invention at different thicknesses; Figure 4 It can be seen that when the matching thickness is 3.56 mm, the lowest reflection loss (RL) at 5.05 GHz (C-band) is... min The effective absorption bandwidth (EAB) is -66.99 dB, and when the matching thickness is 1.98 mm, the effective absorption bandwidth (EAB) is 7.95 GHz (8.3-16.25 GHz), covering most of the X-band and Ku-band.
[0041] The CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared in Example 3 was mixed with paraffin at a mass ratio of 25:100, placed in a mold, and pressed into a coaxial ring. Figure 5 This is a reflection loss diagram of the CF@conductive MOF@Fe3O4 film prepared in Example 3 of the present invention at different thicknesses; Figure 5 It can be seen that when the matching thickness is 4.72 mm, the lowest reflection loss (RL) at 6.88 GHz (C-band) is... min The effective absorption bandwidth (EAB) is -53.14 dB, and with a matching thickness of 2.58 mm, it is 6.32 GHz (11.68-18 GHz), covering part of the X-band and the entire Ku-band.
[0042] The CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film prepared in Example 4 was mixed with paraffin at a mass ratio of 15:100, placed in a mold, and pressed into a coaxial ring. Figure 6 This is a reflection loss diagram of the CF@conductive MOF@Fe3O4 film prepared in Example 4 of this invention at different thicknesses; Figure 6 It can be seen that when the matching thickness is 3.59 mm, the lowest reflection loss (RL) at 17.76 GHz (Ku band) is... min The effective absorption bandwidth (EAB) is -35.76 dB, and when the matching thickness is 3.74 mm, the effective absorption bandwidth (EAB) is 4.96 GHz (9.68-14.64 GHz), covering part of the X-band and Ku-band.
[0043] The CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared in Example 5 was mixed with paraffin at a mass ratio of 25:100, placed in a mold, and pressed into a coaxial ring. Figure 7 This is a reflection loss diagram of the CF@conductive MOF@Fe3O4 film prepared in Example 5 of this invention at different thicknesses; Figure 7 It can be seen that when the matching thickness is 2.25 mm, the lowest reflection loss (RL) at 17.8 GHz (Ku band) is... min The effective absorption bandwidth (EAB) is -20.37 dB, and when the matching thickness is 2.84 mm, the effective absorption bandwidth (EAB) is 7.85 GHz (10.05-17.9 GHz), covering part of the X-band and Ku-band.
[0044] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments. It should be noted that many modifications and improvements can be made by those skilled in the art, and all modifications or improvements not exceeding the scope of the claims should be considered within the protection scope of the present invention.
Claims
1. A method for preparing a CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing film, characterized in that, Includes the following steps: Step 1: Dissolve the polymer in an organic solvent, mix and stir until clear to obtain an electrospinning solution, electrospin to obtain a polymer film, then pre-oxidize and carbonize the polymer film at high temperature to obtain carbon fiber, then heat, wash and dry the carbon fiber in a mixed acid system to obtain mixed acid treated carbon fiber. Step 2: Dissolve the metal salt and 2,3,6,7,10,11-hexahydroxytribenzene in deionized water, then add carbon fibers treated with mixed acid, place in a sealed reaction vessel and heat, naturally cool to room temperature, wash with acetone and deionized water, and vacuum dry to load a conductive MOF on the surface of the carbon fiber matrix, denoted as CF@conductive MOF film. Step 3: Using a chemical co-precipitation method, ferric salts and ferrous salts are used as iron sources, and 25wt% ammonia water is used as a precipitant. The CF@conductive MOF membrane is added and stirred in a water bath. After the reaction is completed, the membrane is washed multiple times with deionized water and anhydrous ethanol, and then vacuum dried. Fe3O4 nanoparticles are loaded on the surface of the conductive MOF in the CF@conductive MOF membrane to obtain the CF@conductive MOF@Fe3O4 three-layer composite microwave absorbing membrane.
2. The method for preparing the CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 1, characterized in that, The polymer mentioned in step 1 is polyacrylonitrile, the organic solvent is N,N-dimethylformamide, and the mixed acid system is sulfuric acid and nitric acid; the metal salt mentioned in step 2 is one or more of zinc acetate, copper acetate, cobalt acetate, and nickel acetate; the trivalent ferric salt mentioned in step 3 is ferric chloride hexahydrate, and the divalent ferric salt is ferrous chloride tetrahydrate.
3. The method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 2, characterized in that, The electrospinning solution contains 10-15% polyacrylonitrile by mass, has a molecular weight of 150,000, a stirring speed of 1000-1100 r / min, and a stirring time of 10-12 h.
4. A method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 1 or 2, characterized in that, The parameters for electrospinning in step 1 are: voltage 15-20 kV, solution propulsion rate 0.1-0.15 mm / min, receiving distance 10-25 cm, temperature 22-30 ℃, and humidity 45-55%.
5. A method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 1 or 2, characterized in that, The parameters for the pre-oxidation process in step 1 are: temperature 230-260 ℃, holding time 1-3 h; the parameters for the high-temperature carbonization process are: temperature 700-900 ℃, holding time 3-5 h, atmosphere is nitrogen or argon, and heating rate is 2-5 ℃ / min.
6. The method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 2, characterized in that, In the mixed acid system of step 1, the volume ratio of sulfuric acid to nitric acid is (2-4):1, the mass concentration of sulfuric acid is 95.0%~98.0%, the mass concentration of nitric acid is 65.0%~68.0%, the carbon fiber is heated in the mixed acid system at a temperature of 30-70 ℃ for 1-4 h, and the size of the carbon fiber is 2cm×4cm.
7. A method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 1, 2, or 6, characterized in that, In step 2, the amount of metal salt used is 0.035-0.045 g, the amount of 2,3,6,7,10,11-hexahydroxytriphenyl is 0.025-0.030 g, the amount of deionized water is 14-18 mL, the heating temperature is 80-90 ℃, and the heating time is 10-14 h.
8. The method for preparing a CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 7, characterized in that, In step 3, the amount of ferric chloride hexahydrate is 0.6-0.9 g, the amount of ferrous chloride tetrahydrate is 0.3-0.5 g, the amount of deionized water is 70-90 mL, the amount of 25wt% ammonia water is 8-10 mL, and the water bath stirring temperature is 50-70 ℃ and the time is 1-3 h. In steps 2 and 3, the vacuum drying temperature is 50-70 ℃ and the drying time is 10-12 h.
9. A CF@conductive MOF@Fe3O4 three-layer composite absorbing film prepared by the preparation method of any one of claims 1-8.
10. The application of the CF@conductive MOF@Fe3O4 three-layer composite absorbing film according to claim 9 in the field of microwave absorption, characterized in that, The CF@conductive MOF@Fe3O4 three-layer composite absorbing film was mixed with paraffin wax at a mass ratio of (10-25):100, and then placed in a mold to press into a coaxial ring with an inner diameter of 3.04 mm and an outer diameter of 7.0 mm.